Influence of System Parameters on Nonlinear Dynamic Characteristics of the Herringbone Gear Transmission Under Different Coincidence Degrees - Wang Ji; Li Zhibin; Wang Sanmin; Wang Chunling (Jixie chuandong)
The coincidence degree is an important parameter to reflect the number of meshing teeth of gear pairs at the same time. The appropriate coincidence degree of reasonable selection can improve transmission bearing capacity and ensure transmission stability, thereby improving the performance and reliability of the gear transmission system. The analysis of the influence of system parameters on system vibration characteristics under different coincidence degrees is of great significance for optimizing the transmission system performance, improving work efficiency and reducing fault risk. Combining meshing performance and dynamic characteristics of gear teeth, firstly, stiffness excitation and meshing impact excitation of the herringbone gear system are determined, and the lumped parameter method is used to establish the nonlinear dynamic model of the bending-torsion-shaft coupling of herringbone gear pairs under complex excitation source. Then, the nonlinear dynamic equations are subject to elimination of rigid body displacement and dimensionless treatment. Finally, the influence of system parameters on system dynamic characteristics under different coincidence degrees is studied. The research shows that when the coincidence degree changes from 2.72 to 3.08, the root mean square (RMS) value of comprehensive relative vibration acceleration of the gear pair is reduced by about 40%, which shows that increasing the coincidence degree can improve the stability of the gear system. In addition, with the change of system parameters, increasing coincidence degree can eliminate the jump phenomenon in the system and reduce the amplitude of jump and resonance peak.